Decolonial Theory in East Asia? Outlining a Shared Paradigm of Epistemologies of the South. - Serrano-Muñoz,Jordi (2021)
Abstract This paper explores the challenges and potentialities of establishing a shared paradigm of transformative knowledge based on the dialogue between East Asian experiences and the rest of the global South, particularly Latin America. It gathers and organizes a general overview of significant attempts of framing East Asian struggles within resistances against Western hegemonic epistemological impositions. It makes the case for seeking shared links and critical differences that can help to incorporate East Asian experiences within the paradigm of epistemologies of the South. This study also problematizes the articulation of a propositional methodology of comparison that could nurture the production of local, decolonial approaches and foster the exchange of practices and knowledges from and to East Asia.